2004
DOI: 10.1016/s0021-9290(03)00235-5
|View full text |Cite
|
Sign up to set email alerts
|

Muscle force is determined also by muscle relative position: isolated effects

Abstract: Effects on force of changes of the position of extensor digitorum longus muscle (EDL) relative to surrounding tissues were investigated in rat. Connective tissue at the muscle bellies of tibialis anterior (TA), extensor hallucis longus (EHL) and EDL was left intact, to allow myofascial force transmission. The position of EDL muscle was altered, without changing EDL muscle-tendon complex length, and force exerted at proximal and distal tendons of EDL as well as summed force exerted at the distal tendons of TA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(77 citation statements)
references
References 47 publications
(52 reference statements)
0
75
1
Order By: Relevance
“…Substantial proximo-distal force differences were shown also for active EDL muscle with epimuscular connections (i.e., the integral system of inter-and extramuscular connections). The length of active EDL muscle was kept constant whereas, (1) the lengths of the active synergistic tibialis anterior (TA) and extensor hallucis longus (EHL) muscles (Maas et al 2001) or that of active EHL muscle exclusively (Yucesoy et al 2006b) were manipulated (2) the relative position of active EDL muscle with respect to nonmuscular tissues Yucesoy et al 2006b), as well as both muscular and nonmuscular tissues (Maas et al 2004) were altered to yield unequal proximal and distal forces. Therefore, the proximo-distal force differences are a consequence of epimuscular myofascial force transmission from the muscle and such force differences shown presently for the aponeurotomized muscle modeled with intact extramuscular connections are likely to occur also experimentally.…”
Section: Proximo-distal Force Differencesmentioning
confidence: 99%
“…Substantial proximo-distal force differences were shown also for active EDL muscle with epimuscular connections (i.e., the integral system of inter-and extramuscular connections). The length of active EDL muscle was kept constant whereas, (1) the lengths of the active synergistic tibialis anterior (TA) and extensor hallucis longus (EHL) muscles (Maas et al 2001) or that of active EHL muscle exclusively (Yucesoy et al 2006b) were manipulated (2) the relative position of active EDL muscle with respect to nonmuscular tissues Yucesoy et al 2006b), as well as both muscular and nonmuscular tissues (Maas et al 2004) were altered to yield unequal proximal and distal forces. Therefore, the proximo-distal force differences are a consequence of epimuscular myofascial force transmission from the muscle and such force differences shown presently for the aponeurotomized muscle modeled with intact extramuscular connections are likely to occur also experimentally.…”
Section: Proximo-distal Force Differencesmentioning
confidence: 99%
“…Therefore, their muscle-tendon complex lengths were also kept constant. In this way, effects of changes of length and relative muscle position of these muscles on force transmission from EDL III (Huijing and Baan 2003;Maas et al 2001Maas et al , 2004 were excluded.…”
Section: Experimental Protocolsmentioning
confidence: 99%
“…Local high strains and stresses at the interface between muscle bellies. If a single muscle-tendon complex is lengthened, shearing of the interface between the corresponding muscle belly and adjacent tissues is highest near the location at which length changes are imposed and gradually decreases to the opposite site (for a schematic illustration see Maas et al 2004). Thus very local differences in shear strain are expected and, if equal shear stiffness of the connective tissues between a muscle head and adjacent tissues is assumed, local differences in shear stress.…”
Section: Intermuscular Myofascial Force Transmission In Dynamic Musclmentioning
confidence: 99%
See 1 more Smart Citation
“…Myofascial connections between a muscle's epimysium and surrounding structures can also transmit force (Huijing, 2009;Maas and Sandercock, 2010). Several studies, in which muscles within the rat anterior crural compartment were excited maximally and their tendons were severed from the skeleton, have shown that forces exerted at the tendon of a muscle kept at a constant muscletendon unit (MTU) length were dependent on the neighboring muscle's length (Huijing and Baan, 2008;Huijing et al, 2007;Maas et al, 2005;Meijer et al, 2006;Rijkelijkhuizen et al, 2007) or relative position (Maas et al, 2004). However, several of these imposed changes were beyond those found during normal movement.…”
Section: Introductionmentioning
confidence: 99%